2019
DOI: 10.15406/jpcpy.2019.10.00650
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia among long-term drug users: a pilot study in Oporto

Abstract: Increasing scientific evidence supports an association between alexithymia and psychoactive substance use. This study explores alexithymia´s expression in sample of long-term drug users, undergoing outpatient treatment in public health units in Oporto, Portugal, as well as its´ association with social demographic risk factors. Data was collected from a sample of 90 adults, participants, mainly men (n=90; 87%), considered to be old consumers (81% with a age>40 years), with a mean age of 46.1 years (SD=8.3; r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A previous study on alexithymia amongst long-term drug users found elevated rates of the condition in their subjects, suggesting a high incidence of emotional awareness deficits that impede the growth of institutional and familial support networks with significant ramifications for developing social integration plans (at the work and family levels) that safeguard quality of life. (Souto, Alves, Conde, Pinto, & Ribeiro, 2019). These drawbacks affect patients' readiness to change their addictive state and complicate the situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study on alexithymia amongst long-term drug users found elevated rates of the condition in their subjects, suggesting a high incidence of emotional awareness deficits that impede the growth of institutional and familial support networks with significant ramifications for developing social integration plans (at the work and family levels) that safeguard quality of life. (Souto, Alves, Conde, Pinto, & Ribeiro, 2019). These drawbacks affect patients' readiness to change their addictive state and complicate the situations.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, they must incorporate particular psychotherapeutic techniques that encourage both the recognition and the variation in emotionally dysfunctional patients. (Souto, Alves, Conde, Pinto, & Ribeiro, 2019). This effort may have a great effect on increasing patients' readiness to change and heighten their motivation for treatment.…”
Section: Discussionmentioning
confidence: 99%